Soft Starting of a Modified Three-Phase Induction Motor with a Single-Phase Synchronous PWM AC Chopper - Chavaporn Bumroongphuck; Rangsan Koodsamrong; Vijit Kinnares (My University, 2025)
This paper presents a soft starting method for a modified three-phase induction motor using a single-phase synchronous PWM AC chopper to reduce starting current and electromagnetic torque pulsation. The modified motor functions as a single-phase induction motor due to the lack of a three-phase source and employs an appropriate capacitor. The synchronous single-phase PWM AC chopper provides several benefits over traditional thyristor soft starters, including a linear relationship between fundamental voltage and modulation index, improved voltage control, and lower harmonic currents. A cost-effective microcontroller gradually increases the duty cycle to create PWM signals for soft starting, achieving nearly a 65% reduction in starting current compared to direct online starting. Simulation and experimental results confirm enhanced starting performance, making it suitable for applications such as water and air pumps.
Keywords: Electric Power Systems and Control; Diverse Industrial Engineering Technologies; Induction Heating and Inverter Technology